DESIGN AND TESTING OF PROTOTYPE NEW WATER TREATMENT PLANT (NWTP) PT KRAKATAU TIRTA INDUSTRI LABORATORY SCALE - Diva Rasida, Sabrina
PT Krakatau Tirta Industri (KTI) is a company engaged in water supply and treatment. PT KTI has two treatment plants to meet the needs of clean water for the community and industry in Cilegon City. However, over time, the need for clean water, especially for industrial purposes, continues to increase. Therefore, PT KTI plans to increase production capacity, by building a New Water Treatment Plant (NWTP) with a capacity of 600 L/sec. The Basic Engineering Design (BED) document for the NWTP has been prepared and will be continued with the preparation of Detail Engineering Design (DED) supported by laboratory studies using laboratory scale models (prototypes). The prototype that will be tested consists of combined units, namely Aero-Coagulator and Clearator which represent aeration, coagulation, flocculation, and sedimentation processes. The prototype is designed with a scale of 1:1000 of the original capacity. This study was conducted to determine the prototype conditions, hydraulic conditions, and processing conditions. Based on the study, the prototype is able to drain water from the raw water tank to the treated water tank. However, there is water loss due to leakage and water jumping in the range of 10% - 28%. The water loss was measured and it was found that the lowest water loss occurred at a capacity of 8 L/min, so the optimum capacity determined in this study was 8 L/min. The apparent residence time was also determined based on hydraulic experiments using a tracer solution. It was found that the real residence time of the treatment was about 380 minutes. The last experiment was conducted to determine the treatment process. Treatment experiments were conducted for three raw water conditions, namely original raw water, raw water with high turbidity, and raw water with high color. Jar tests were conducted for all three conditions with the optimum dose of coagulant in the range of 60 - 80 ppm. The treatment experiment showed good results (reaching the target) with the achievement of turbidity concentration of 2.5 NTU, color of 2 Pt-Co, and iron (Fe) of 0.18 mg/L.